AIAA Scitech 2021 Forum 2021
DOI: 10.2514/6.2021-0883
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning based Online Adaptive Flight Control for the Cessna Citation II(PH-LAB) Aircraft

Abstract: Online Adaptive Flight Control is interesting in the context of growing complexity of aircraft systems and their adaptability requirements to ensure safety. An Incremental Approximate Dynamic Programming (iADP) controller combines reinforcement learning methods, optimal control and online identified incremental model to achieve optimal adaptive control suitable for Nonlinear Time-Varying systems. The main contribution of this paper is twofold. Firstly, the iADP controller is designed to achieve automatic onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…During [34]. This step-by-step clearance of different subsystems of iADP FCL ensured the analysis and rectification of any issues found with individual subsystems.…”
Section: Clearance Of Control Laws Through Verification and Validatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…During [34]. This step-by-step clearance of different subsystems of iADP FCL ensured the analysis and rectification of any issues found with individual subsystems.…”
Section: Clearance Of Control Laws Through Verification and Validatio...mentioning
confidence: 99%
“…The following desirable features for the control method are defined as follows: a simpler control design strategy with less and interpretable learning parameters, ability to adapt in real-time to fast changing nonlinear dynamics of aircraft in case of a failure, an algorithm which is sample efficient [13] [14] and fast to converge on the conventional Flight Control Computer (FCC). In this regard, iADP based FCS [15] is a good choice amongst the RL based FCS with practical interests. This algorithm identifies a local linearized incremental model online, to estimate and minimize an infinite horizon quadratic cost-to-go, exclusively using the collected aircraft state data [16].…”
Section: Introductionmentioning
confidence: 99%
“…A policy objective with an expectation over noise instead of an expectation over actions, making use of the Q-function as an approximation of expected future rewards and entropy, is introduced in Eq. (9).…”
Section: Policymentioning
confidence: 99%
“…Longitudinal control was proposed first by [7], and then the introduction of Incremental Dual Heuristic Programming (IDHP) demonstrated fault-tolerance on simple failure cases [8]. Using IDHP for coupled-dynamics body rate control, [9] showed that that a business jet aircraft could be controlled successfully. It was extended to altitude and attitude control with pre-tuned PID controllers in [10] and [11], yet as the longitudinal and lateral motions were decoupled severe failures cases where the coupling effects become too dominant were not tested.…”
Section: Introductionmentioning
confidence: 99%